Inferring HIV-1 transmission networks and sources of epidemic spread in Africa with deep-sequence phylogenetic analysis - Oliver Ratmann (Nature Portfolio, 2019)
Here, Ratmann et al. show how viral deep sequencing data can be used to reconstruct HIV-1 transmission networks and to infer the direction of transmission in these networks.